Points of Zero Charge and Potentiometric Titrations - Tao Zuyi; Chu Taiwei (Adsorption Science & Technology)
Based on the various categories of surface charge and the definitions of points of zero charge proposed by Sposito (1984, 1998), the determination of the adsorbed proton charge (σ H ) and the point of zero net charge (PZNPC) of insoluble oxides and layer silicates in aqueous solution was examined in detail using potentiometric titration experiments. The confusion, various interpretations and difficulties associated with points of zero charge, including the point of zero net proton charge (PZNPC), the point of zero net charge (PZNC) and the point of zero charge (PZC), were discussed and clarified. The importance of comparing potentiometric titration curves for pure insoluble oxides in the presence and absence of specific adsorption and of layer silicates with a permanent negative charge was emphasized. The dependency of expressions of points of zero charge on the model assumed and the weakness of the method of potentiometric titrations widely used for the determination of points of zero charge were discussed.